2010
DOI: 10.1016/j.joen.2010.06.020
|View full text |Cite
|
Sign up to set email alerts
|

Frequency of Nonodontogenic Pain after Endodontic Therapy: A Systematic Review and Meta-Analysis

Abstract: Introduction-Little is known about ill-defined pain that persists following endodontic procedures, including an estimate of the problem's magnitude. We conducted a systematic review of prospective studies that reported the frequency of non-odontogenic pain in patients who had undergone endodontic procedures.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
52
0
3

Year Published

2011
2011
2021
2021

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 89 publications
(58 citation statements)
references
References 31 publications
3
52
0
3
Order By: Relevance
“…Several articles that met the inclusion criteria were not included in the meta-analyses because specific posttreatment time intervals were not reported (37,46,47,55,90). Recent systematic reviews have shown that 6 months after root canal treatment the frequency of persistent tooth pain of all causes was low, approximately 5%, and the frequency of nonodontogenic pain was approximately 3% (11,12). These data were consistent with the findings of this current study insofar as they overlap.…”
Section: Review Articlesupporting
confidence: 85%
See 1 more Smart Citation
“…Several articles that met the inclusion criteria were not included in the meta-analyses because specific posttreatment time intervals were not reported (37,46,47,55,90). Recent systematic reviews have shown that 6 months after root canal treatment the frequency of persistent tooth pain of all causes was low, approximately 5%, and the frequency of nonodontogenic pain was approximately 3% (11,12). These data were consistent with the findings of this current study insofar as they overlap.…”
Section: Review Articlesupporting
confidence: 85%
“…However, the extant literature containing data on endodontic pain is rather disparate and primarily includes articles focusing on other topics, typically prognostic variables, treatment variables, or medications (8,9). Direct comparisons of pretreatment, treatment, and posttreatment pain are extremely rare (10)(11)(12). Thus, it is difficult for the dentist to identify, assimilate, or synthesize data on root canal treatment-associated pain in a clinically applicable manner.…”
mentioning
confidence: 99%
“…15,19 Our body produces antiinfl ammatory such as cortisol, thus to keep in homeostasis, our body has the propensity to compensate noxious stimuli, proinflammatory mediators or neutralize antigens by itself. 5,8,9 Based on Psychoneuroimmunology concept, in stressful individuals, cortisol level increased and plays a synergistic role with proinfl ammatory cytokines instead of suppressing them. 12,15,16 This idea was supported with the facts that antidepression therapy relieves the pains.…”
Section: Discussionmentioning
confidence: 99%
“…These therapies are common attempts to decrease pain, but also cause more complications for patients and legal affairs for dentists. 4 Nixdorf et al, 5 study showed that 27.27% patients suffered from persistent tooth pain after root canal therapy which may be exaggerated by pulpal extirpation and became neuropathic tooth pain (NTP). Interestingly, the prevalence of persistent pain occurred in the maxillary teeth were 87.5% compared to 12.5% in the mandibular teeth, and 68.8% relieved by tricyclic depressants.…”
Section: Introductionmentioning
confidence: 99%
“…1,125 had follow-up information regarding pain status. The authors identified nonodontogenic pain in 3.4% (95% confidence interval, 1.4%-5.5% frequency of occurrence) 43 .…”
Section: Persistent Post Surgical Pain Without Demonstrable Neuropathymentioning
confidence: 99%